Dosage compensation and nuclear organization: cluster to control chromosome-wide gene expression. (April 2016) - Sharma, Rahul; Meister, Peter
Abstract : In many species, male and female animals differ in the number of X chromosomes they possess. As a consequence, large scale differences in gene dosage exist between sexes; a phenomenon that is rarely tolerated by the organism for changes in autosome dosage. Several strategies have evolved independently to balance X-linked gene dosage between sexes, named dosage compensation (DC). The molecular basis of DC differs among the three best-studied examples: mammals, fruit fly and nematodes. In this short review, we summarize recent microscopic and chromosome conformation capture data that reveal key features of the compensated X chromosome and highlight the events leading to the establishment of a functional, specialized nuclear compartment, the X domain.